Pleiotropic effects of vitamin D3 - Dominika Egierska; Paulina Pietruszka; Paulina Burzyńska; Izabela Chruścicka; Justyna Buchta (Kazimierz Wielki University, 2021)
Introduction: Vitamin D belongs to the group of fat-soluble vitamins. cholecalciferol (D3) and ergocalciferol (D2) are the most important forms. Vitamin D is associated with a regulatory role in calcium and phosphate metabolism. In recent years, there has been attention to its pleiotropic action.  Aim: The aim of the study was to present the general characteristics of vitamin D and explore its relation with polycystic ovary syndrome (PCOS), endometriosis, pain management, insulin resistance, influenza and chronic kidney disease (CKD). Description: VDR receptor has been detected in the cells of the intestines, bones, kidneys, heart, brain, prostate, breast, ovaries, skin. In the ovaries, vit. D3 affects the production of progesterone, estradiol or estrone which suggest its important role in the folliculogenesis and ovulation. Women with PCOS have significantly lower levels of vitamin D3 compared to healthy women. It has been suggested that the deficiency of this vitamin may be related to infertility. Research show that vit. D3 may affect the mechanisms of the inflammatory and nocyceptive pain perception. A significant connection has also been found between vit. D3 and the metabolism of the adipose tissue and insulin secretion. Vitamin D3 deficiency may increase the risk of development of obesity and insulin resistance as well as CKD. Summary: The observation of statistically significant correlation between the reduced level of vit. D3 and occurrence of numerous diseases indicates the need for further research to explain the mechanisms in which D3 deficiency may contribute to development of these diseases. This knowledge is important for the development of new prevention and treatment methods of the diseases mentioned in this article.